Numerical Solution of European Put Option for Black-Scholes Model Using Keller Box Method - Mardianto, Lutfi; Putra, Gusrian; Pratama, Benediktus Ivan; Putri, Endah R. M. (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2024)
In this study, we propose to determine option pricing by using Black-Scholes model numerically. The Keller box method, a numerical method with a box-shaped implicit scheme, is chosen to solve the problem of pricing stock options, especially European-put option. This option pricing involves several parameters such as stock price volatility, risk-free interest rate and strike price. The numerical stability of the method is checked using Von Neumann stability before the simulation is conducted. The influence of interest rates, volatility, and strike price on the option price state that the higher the value of the interest rate parameter, the lower the option price value, while the greater the value of stock price volatility and strike price, the higher the option price.